2019
DOI: 10.1097/dss.0000000000001700
|View full text |Cite
|
Sign up to set email alerts
|

Underappreciated Utility of the Purse-String Suture in Head and Neck Skin Cancer Defect Reconstruction

Abstract: BACKGROUND The purse-string suture (PSS) is a simple, reversible method for reconstructing skin cancer defects. Its utility may be underappreciated in head and neck reconstructive surgery. OBJECTIVE To evaluate the utility of the PSS as an adjunct to the reconstructive ladder when reconstructing head and neck skin cancer defects. MATERIALS AND METHODS This prospective nonrandomized cohort included 109 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Moreover, PSS allows the original defect size reduction, with a decrease quantifiable in 77.1% in a prospective nonrandomized cohort of 109 patients, 1 which was confirmed by a reduction of 73% in our results. This guarantees the possibility of performing, if necessary, an additional minor intervention in order to complete the closure of the surgical breach 1,14 …”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Moreover, PSS allows the original defect size reduction, with a decrease quantifiable in 77.1% in a prospective nonrandomized cohort of 109 patients, 1 which was confirmed by a reduction of 73% in our results. This guarantees the possibility of performing, if necessary, an additional minor intervention in order to complete the closure of the surgical breach 1,14 …”
Section: Discussionsupporting
confidence: 83%
“…To the best of our knowledge, this is the first study that compares the efficacy and usefulness of the two different surgical techniques (PSS vs FTSG) in the closure of surgical defects in nondistensible areas, even if numerous previous studies reported PSS as a useful procedure to reduce the residual surgical area, needing a smaller size skin graft. [1][2][3]12 In our experience, the PSS technique proved to be a quick and easy procedure to close or approximate cutaneous skin defects after NMSC excision. Operative times were significantly reduced compared to those needed for FTSG, without perioperative adverse events and excellent hemostatic control, 13 even if the PSS requires a waiting time before removing the suture greater than FTSG.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations